Soil Enzyme Responses to Polymeric Nanopesticides: An Ecological Risk Analysis Approach to Promote Sustainable Agriculture - Galhardi, Juliana Aparecida [UNESP] (2022)
The benefits of the use of green nanotechnology to improve food security and sustainable agriculture have been highlighted in the past few years, such as through the encapsulation of active ingredients derived from botanical compounds. To evaluate ecological risks and to contribute to the development of safer nanoparticles for use in agricultural applications, this paper focused on the effects of the encapsulation of two mixtures of botanical pesticides (geraniol (GRL) and eugenol (EGL), and GRL and cinnamaldehyde (CND); concentration of active ingredients (a.i.) of 5, 20, and 100 mg a.i./kg-1) into zein nanoparticles on soil enzyme activities (acid phosphatase, arylsulfatase, β-1,4-glucosidase) at different incubation times (2, 7, 14, 21, and 28 days). Soils were also treated with pure zein nanoparticles at the same concentrations as those of the nanoformulations. The control samples consisted of untreated soils. Acid phosphatase was the most sensitive enzyme to the nanopesticide formulations applied at a high dosage (100 mg kg-1) following 2 weeks of the exposure, whereas arylsulfatase and β-1,4-glucosidase showed no significant responses to increasing doses of the nanopesticides, indicating soil enzyme resilience after pesticide exposure. Different concentrations of salt (NaCl; 0.01-0.4 mol L-1pH 7), humic acid (5-20 mg L-1pH 7), and pH (5-9) were shown to affect nanopesticides' properties in solution (e.g., particle diameter increased with the increase of the ionic strength, humic acid, and pH). Such results underline the potential uses of hydrolases as indicators of the soil quality and resilience as well as the effects of characteristics of a soil solution on particles' dynamics, mobility, and toxicity, which have important implications to assess soil health in response to botanical nanopesticides.